The Importance of Health Care Providers in Improving the Outcomes of Liver Patients - Faisal Hunaythil Almuraykhi,; Shifaa Rida Alshaban,; Khalil Ibrahim Aljuffali,; Abdullah Ali Saleh Alwaqisi,; Majed Abdrabalrasool Al Sager,; Ahmad Habib Ali Aljomia,; Sukina Ebrahim Alradwan,; Hussain Essa Ali Alsalim,; Hawra Khudhair Aldhamin,; Zahrah Ali Ahmad Al Ali, (International Journal of Medical Toxicology and Legal Medicine, 2024)
According to the Centers for Disease Control & Prevention, an estimated 2.7–3.9 million individuals in the United States are currently afflicted with chronic hepatitis C virus (HCV). It is assessed that around twenty-five percent of individuals in the United States who are living with human immunodeficiency virus ([HIV] PLWH) are additionally living with hepatitis C virus. PLWH who are living with hepatitis C virus are at an elevated possibility of rapid progression of decompensated hepatic illness & hepatic fibrosis, as demonstrated by numerous studies. Chronic liver diseases have become a significant global challenge as a result of their elevated occurrence, significant burden on healthcare systems, and marked death rates. Conversely, the role of nurses in treatment of cases who have hepatic illnesses is less well-developed in numerous countries than it is in the case of other chronic conditions, involving chronic obstructive pulmonary illness, diabetes mellitus & heart failure. In the past, it has been discovered that cases with hepatitis C virus & cirrhosis utilize healthcare services more frequently due to the presence of advanced illness. Although illnesses & medical comorbidities account for a significant portion of differences in readmission rates & costs, they don’t entirely elucidate the situation. It is intriguing that a recent effort to standardize and optimize management of chronic illness was unsuccessful in reducing readmissions or enhancing the quality of life of cases having chronic liver illness.